A20 restricts inflammation via ubiquitin binding - Sun, Shao-Cong (Nature immunology, 2020)
The ubiquitin-editing enzyme A20 has a pivotal role in restricting autoimmune and inflammatory responses. New studies suggest that A20 prevents inflammatory diseases using a non-catalytic mechanism involving ubiquitin binding.